Effects of Income and Psychological Identification on the Mental Health of China's Migrated Agricultural Population - Jing XU; Yue TIAN; Siting WANG; Yixuan LU (Tehran University of Medical Sciences, 2018)
Background: The Migrated Agricultural Population (MAP) of China continues to increase with the continuous development of urbanization. As MAP is a socially disadvantaged group, their mental health issues require urgent attention. Methods: An ordinary least squares regression model was established by using the newest survey data from the 2016 Chinese General Social Survey. Moreover, the effects of income and psychological identification on the mental health status of China's MAP were also examined using the Stata 12.0 software. The differences in the examination results under the influence of gender, educational level, and marital factors were compared. Results: The mental health level of China's MAP is affected by both income and psychological identification. Specifically, income has a more significant influence on men's mental health, whereas psychological identification is more significant for women. The mental health of MAP with spouses or those who received secondary education also reflects the overall characteristics of the sample. By contrast, those without spouses or those who did not receive other forms of education are mainly affected by psychological identification. Additionally, the mental health of the unmarried group is mainly affected by the family's actual income and subjective well-being based on the psychological identification. Conclusion: The influence of income and psychological identification on the mental health of China's MAP shows population differences. Therefore, different emphasis should be placed on the interventions of mental health in various groups of MAP. This study can provide decision-making references for the mental health management and psychological pressure counseling of MAP.